Direct Modelling CAD Technology Comparative Review In Efficiency And Productivity For Product Development Process - Mohd Qadafie, Ibrahim; Nurulhalim, Hassim; Ahmad Anas, Yusof; Siti Zulaikha , Abdul Mutalib (Trans Tech Publications, 2015)
Direct modelling is a new CAD technology that enables model geometry construction by pushing, pulling or twisting which emphasis to solve the constraint issues made by the current technology. Ideally it is more efficient and productive in accomplishing a part of product development process. Parametric modelling is set as the benchmark. This study is about comparing productivity and efficiency of both modelling by mean of counting mouse button clicks as representing speed for accomplishing the task. The review also taking into account several qualitative aspects during the process. Consequently, direct modelling is proven better from the parametric modelling for this scenario.